PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GAMIFIKASI PADA MATERI SIKLUS AIR KELAS V SISWA SEKOLAH DASAR - Septia Rahma Putri; Dwi Cahaya Nurani; Suratmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop interactive gamification-based learning media for the water cycle topic in fifth-grade elementary school science. The background of the research is the lack of engaging and interactive media in science learning, which affects students' motivation and conceptual understanding. This research employed the ADDIE development model, consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The trial subjects were students of Class V.A at SD Negeri 14 Indralaya Utara. Data collection techniques included interviews, observations, documentation, validation sheets, and questionnaires. The validation results showed that media experts gave a score of 97.5%, subject matter experts also gave 97.5%, and two practitioners gave 91.6%. The average validation score from all validators was 91.6%, categorized as “very valid.” The media was then tested through one-to-one trials with a result of 96.6% and small group trials with a result of 95.5%. The average practicality score was 95.8%, categorized as “very practical”. The developed media includes features such as narration, animation, interactive quizzes, levels, rewards, and feedback. The results concluded that the gamification-based learning media is valid, practical, and effective in enhancing students' understanding and learning motivation. This product is recommended to support science learning aligned with the Merdeka Curriculum in elementary schools.